Optimisation of composite bone plates for ulnar transverse fractures - Chakladar, N. D; Harper, Lee Thomas; Parsons, A. J. (Elsevier, 2016)
Metallic bone plates are commonly used for arm bone fractures where conservative treatment (casts) cannot provide adequate support and compression at the fracture site. These plates, made of stainless steel or titanium alloys, tend to shield stress transfer at the fracture site and delay the bone healing rate. This study investigates the feasibility of adopting advanced composite materials to overcome stress shielding effects by optimising the geometry and mechanical properties of the plate to match more closely to the bone.